The Effect of Teacher Competency Learning Administration and School Quality on The Achievement of Student SMPN1 Kragilan - Siti Kusmaryeni; Habibah Habibah; Saefudin Saefudin; Romli Ardie; Ali Imron (Yayasan Pendidikan Riset dan Pengembangan Intelektual (YRPI), 2026)
The purpose of the study was to examine the influence of learning administration, teacher competence, and school quality on achievement with objects at SMPN1 Kragilan. Using quantitative methods through a descriptive approach. Respondents were 40 teachers with saturated sampling. Using questionnaire instruments distributed to respondents, the analysis used the SPSS statistical tool. It was found that effective learning administration such as structured planning, good classroom management, and accurate learning evaluation contributed significantly to improving students' learning achievement abilities. For competencies that include pedagogic aspects, professional aspects, personality aspects, and social aspects also have a significant positive effect on student learning outcomes. For the quality of the school, which is reflected in the availability of facilities, a conducive learning environment, and a strong learning culture, also play an important role in supporting the success of students' learning achievements. Simultaneously, the three variables, namely learning administration, competence, and school quality, are significantly correlated with student achievement. This emphasizes the importance of improving overall school management, sustainable teacher competency development, and equitable distribution of education quality in order to optimize achievement outcomes.